Are Student Absences Worth the Worry in U.S. Primary Schools? - Seth Gershenson; Alison Jacknowitz; Andrew Brannegan (Institute for the Study of Labor (IZA), 2015)
Student absences are a potentially important, yet understudied, input in the educational process. Using longitudinal data from a nationally-representative survey and rich administrative records from North Carolina, we investigate the relationship between student absences and academic performance. Generally, student absences are associated with modest but statistically significant decreases in academic achievement. The harmful effects of absences are approximately linear, and are two to three times larger among fourth and fifth graders in North Carolina than among kindergarten and first-grade students in the nationally representative Early Childhood Longitudinal Study. In both datasets, absences similarly reduce achievement in urban, rural, and suburban schools. In North Carolina, the harm associated with student absences is greater among both low-income students and English language learners, particularly for reading achievement. Also, in North Carolina, unexcused absences are twice as harmful as excused absences. Policy implications and directions for future research are discussed.
Keywords: I21; 330; student absences; attendance; achievement gaps; education production function